2014
DOI: 10.1190/tle33020172.1
|View full text |Cite
|
Sign up to set email alerts
|

An efficient 4D processing flow for variable-depth streamer data

Abstract: Variable-depth streamer acquisition is now widely used, achieving a bandwidth of more than 6 octaves (2.5 to 200 Hz) and excellent lateral resolution and providing improved impedance and reservoir analysis. This acquisition and processing method is based on towing the streamer deep, using a variable-depth profile optimized to ensure receiver notch diversity at the imaging stage and a deghosting method that takes advantage of the notch diversity. For 4D processing of monitors now acquired with variable-depth ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The tau-p model from the inversion in GWE makes it convenient to re-datum the recorded data to a flat datum level which is required for offset binning and demultiple methods. This re-datuming was also the key for successful 4D application with conventional acquisition as a base survey and a VDS as monitor, as demonstrated by Hicks et al (2014). In addition, we have found that GWE can, to a certain extent, be used even on flat-tow streamer data, despite the lack of notch diversity.…”
Section: Receiver Deghostingmentioning
confidence: 82%
“…The tau-p model from the inversion in GWE makes it convenient to re-datum the recorded data to a flat datum level which is required for offset binning and demultiple methods. This re-datuming was also the key for successful 4D application with conventional acquisition as a base survey and a VDS as monitor, as demonstrated by Hicks et al (2014). In addition, we have found that GWE can, to a certain extent, be used even on flat-tow streamer data, despite the lack of notch diversity.…”
Section: Receiver Deghostingmentioning
confidence: 82%
“…Dhelie et al (2014) show data from a snake streamer acquisition, where the receivers are located at different depths, whereas Soubaras and Lafet (2013) explain processing techniques for variable streamer depth acquisition. Additionally, Hicks et al (2014) demonstrate that advanced processing of flat streamer data could reveal results similar to advanced processing of a variable depth streamer. On the other hand, multicomponent receivers are used to measure pressure and particle velocity (Carlson et al, 2007) at the same depth.…”
Section: Introductionmentioning
confidence: 99%
“…Two questions have been frequently raised in the context of 4D time-lapse processing: (1) can we obtain deghosted 4D signals for broader bandwidth and (2) can we apply 4D processing between conventional surveys and broadband surveys? In an attempt to answer both questions, Hicks et al (2014) demonstrated that deghosting was possible and important for 4D processing of multiple vintages with different receiver-depth profiles using a 2D ghost-wavefield elimination algorithm (Poole, 2013). Wang et al (2014) proposed using a progressive sparse Tau-P inversion algorithm for 3D deghosting of singlecomponent marine seismic data.…”
Section: Introductionmentioning
confidence: 99%